Analisis Framing Berita Pencalonan Kandidat Di Portal Berita Online Lokal Di Pilkada Pacitan 2020 - Agoes Hendriyanto; Andrik Purwasito; Wakit Abdullah Rais; Sri Hastjaryo (LPPM Press, 2022)
The research is the framing analysis of candidate nomination news on local online news portals in the 2020 Pacitan pilkada. The purpose of the research is to see how the news of candidate nominations is made on local online portals, namely www.pacitanku.com and www. Lintas7.net in the 2020 Pacitan pilkada. Critical research with Entman framing analysis with issue selection and emphasis and prominence in the news text. The results of the study are as follows.. First, polite politicians with prominence; Gagarin is a polite cadre and Sudijono is a polite politician. Second, the people's cadres, with the highlighting of Gagarin, the people's cadres. Third, successful entrepreneurs with Winarni as a successful entrepreneur. Fourth, the great teacher with the prominence of Sudijono the teacher. Fifth, the development of the agricultural and tourism sectors; with Roni Wahyono's prominence, he plans expert development and agro-tourism development.